2016
DOI: 10.3389/fmars.2016.00133
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Eastern Mediterranean Microbial Ecosystem to Dust and Dust Affected by Acid Processing in the Atmosphere

Abstract: Acid processes in the atmosphere, particularly those caused by anthropogenic acid gases, increase the amount of bioavailable P in dust and hence are predicted to increase microbial biomass and primary productivity when supplied to oceanic surface waters. This is likely to be particularly important in the Eastern Mediterranean Sea (EMS), which is P limited during the winter bloom and N&P co-limited for phytoplankton in summer. However, it is not clear how the acid processes acting on Saharan dust will affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Guo et al, 2012), which reflects the average cellular N : P stoichiometry for oceanic phytoplankton (Arrigo, 2005). Although the deposited P was deficient relative to the demands of the resident phytoplankton in the ocean surface, a few studies showed that the input of dust could compensate for P deficiency to some extent by stimulating the biogenic conversion of dissolved organic P (DOP) to dissolved inorganic P (DIP) or a slow release of DIP from dust (Ridame and Guieu, 2002;Mackey et al, 2012;Krom et al, 2016). This supply of bioavailable P seemingly varies substantially across different oceanic regions and is affected by many factors, including dust sources and its mixing with anthropogenic pollutants, P demand, and the uptake of nutrients that are co-limiting for phytoplankton in the seawater (Mackey et al, 2012).…”
Section: Zhang Et Al: Phytoplankton Growth Response To Asian Dustmentioning
confidence: 99%
“…Guo et al, 2012), which reflects the average cellular N : P stoichiometry for oceanic phytoplankton (Arrigo, 2005). Although the deposited P was deficient relative to the demands of the resident phytoplankton in the ocean surface, a few studies showed that the input of dust could compensate for P deficiency to some extent by stimulating the biogenic conversion of dissolved organic P (DOP) to dissolved inorganic P (DIP) or a slow release of DIP from dust (Ridame and Guieu, 2002;Mackey et al, 2012;Krom et al, 2016). This supply of bioavailable P seemingly varies substantially across different oceanic regions and is affected by many factors, including dust sources and its mixing with anthropogenic pollutants, P demand, and the uptake of nutrients that are co-limiting for phytoplankton in the seawater (Mackey et al, 2012).…”
Section: Zhang Et Al: Phytoplankton Growth Response To Asian Dustmentioning
confidence: 99%
“…On the other hand, nutrients in atmospheric deposition have the potential to stimulate phytoplankton growth in surface oceans (Boyd et al, 2007;Li et al, 2017;Liu et al, 2013). Many previous ship-borne incubation and mesocosm experiments showed stimulation effects on phytoplankton growth, either by directly providing nutrients or by enhancing nitrogen fixation after addition of aerosol samples, including Asian dust (Chu et al, 2018;Krom et al, 2016;Liu et al, 2013;Meng et al, 2016;Mills et al, 2004;Zhang et al, 2018). Previous studies including Duce et al (2008), Mahowald (2011), and Martino et al (2014) also calculated the additional uptake of carbon dioxide (and thus climate effect) due to the nitrogen fertilization effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to new production, it has been shown that leachable nutrients from atmospheric inputs may enhance N 2 fixation, changes in phytoplankton species composition and carbon sequestration (e.g., Mills et al, 2004;Guo et al, 2012;Moore et al, 2013;Bressac et al, 2014;Guieu et al, 2014b;Rahav et al, 2016a). While a low availability of macronutrients (N, P) and metal micronutrients (e.g., Fe, Co) can limit or colimit phytoplankton growth in the ocean (e.g., Moore et al, 2013), high concentrations of some metals (e.g., Cu or Al) can be toxic to phytoplankton (e.g., Paytan et al, 2009;Jordi et al, 2012;Krom et al, 2016). Yet, the impact of these dust inputs on microbial populations has not been fully investigated in the EMS.…”
Section: Introductionmentioning
confidence: 99%